Rehabilitation examination of patients with compression-ischemic neuropathy of the upper limb - Olena Bismak (Kharkiv State Academy of Physical Culture, 2019)
Compression-ischemic neuropathy of the upper limb is a common disease of the peripheral nervous system, accompanied by impaired motor, sensory spheres and a decrease in the quality of life in people of working age. Purpose: to reveal the structure of rehabilitation examination in people with compression-ischemic neuropathy of the upper limb. Material & Methods: analysis and synthesis of data from scientific and methodological literature and the Internet information network; interrogation, history taking, palpation, tests, mathematical methods. The study was conducted on the basis of the neurological departments No. 1 and No. 2 of the Kiev City Clinical Hospital No. 4, Kiev, from 2017 to 2019. The examination involved 48 patients with compression-ischemic neuropathy of the upper limb. Results: a scheme (algorithm) of rehabilitation examination was proposed, which included: a survey, history taking, determining the level of damage, the degree of neurological deficit, motor and sensory disturbances, muscle hypotrophy and atrophy, joint and muscle contracture. During the initial examination of patients with compression-ischemic neuropathy of the upper limb, the predominance of male patients was revealed, namely 89.6%. Damage to the peripheral nerves of the upper limb was more often observed in patients of able-bodied young and middle age - 77,1%. The vast majority were patients with radiation injuries - 52,1% and ulnar nerves - 35,4%. In 60,4% of individuals, pains of moderate intensity were observed (4-6 points on a 10-point visual-analogue scale for assessing pain intensity (VAS)). Conclusions: an initial examination was carried out indicating the presence of disorders of the motor and sensory function of the affected limb in individuals with this pathology. To restore the functional state and preserve the function of the affected limb, it is necessary to comply with the developed scheme (algorithm) of the rehabilitation examination, and will contribute to the development of an effective physical therapy program.